Respuesta :

Answer:

[tex]\frac{(a-b)^2+b^2}{a^{2}}[/tex]

Step-by-step explanation:

see the attached figure to better understand the problem

we know that

The area of the square is

[tex]A=x^{2}[/tex]

where

x is the length side of the square

step 1

Find the area of the outer square (A_o)

we have that

[tex]x=a\ units[/tex]

substitute in the formula

[tex]A_o=a^{2}\ units^2[/tex]

step 2

Find the area of the inner square (A_i)

we know that

The length side of the inner square is equal to the hypotenuse of a right triangle

so

Applying Pythagoras theorem

[tex]x^{2}=(a-b)^2+b^2[/tex]

Remember that

[tex]A_i=x^2[/tex]

so

[tex]A_i=(a-b)^2+b^2[/tex]

step 3

Find the ratio of the area of the inner square to the area of the outer

[tex]ratio=\frac{A_i}{A_o}[/tex]

substitute the values

[tex]ratio=\frac{(a-b)^2+b^2}{a^{2}}[/tex]

Ver imagen calculista
ACCESS MORE